PRMT1-methylated MSX1 phase separates to control palate development - Li Meng; Yucheng Jiang; Jiawen You; Yatao Chen; Shuyu Guo; Liming Chen; Junqing Ma (Nature Communications)
Abstract Little is known about the regulation and function of phase separation in craniofacial developmental disorders. MSX1 mutations are associated with human cleft palate, the most common craniofacial birth defect. Here, we show that MSX1 phase separation is a vertebrate-conserved mechanism underlying embryonic palatal fusion. Notably, MSX1 phase separation is triggered by its intrinsically disordered protein region (IDR) and regulated by PRMT1-catalyzed methylation, specifically asymmetric dimethylation of arginine in the MSX1 IDR including R150 and R157. Hypomethylated MSX1 due to methylation site mutations and PRMT1 deficiency consistently leads to abnormal MSX1 phase separation to form less dynamic gel-like condensates, resulting in proliferation defects of embryonic palatal mesenchymal cells and cleft palate. Besides, high frequency mutations in the MSX1 IDR, especially R157S, have been identified in humans with cleft palate. Overall, we reveal the function and regulatory pathway of MSX1 phase separation as a conserved mechanism underlying cleft palate, providing a proof-of-concept example of a phenotype-associated phase separation mechanism associated with craniofacial developmental disorders.